Multifocal Epithelioid Hemangioma with Reactive Bone Formation. (6th June 2011) - Sin, Jessica M.; Beck, Andrew H.; Pai, Reetesh K.; Stevens, Kathryn J.
Abstract : A healthy 16-year-old male patient presented with several weeks of right ankle pain on weight-bearing, worsened with sporting activities, and relieved with rest. Radiographs demonstrated multiple well-marginated lytic lesions in the right distal tibia, and talar head and neck, with a further small intracortical lesion in the mid-to-distal anterior tibia. MRI showed multiple rounded low T1 and high T2 signal intensity lesions within the distal tibia and talus, with marked associated bone marrow edema. The radiologic diagnoses included multifocal hemangioendothelioma, multifocal hemangioma, angiosarcoma, atypical infection, Langerhans cell histiocytosis, or osteoblastomatosis. Histology showed sheets of epithelioid cells lining vascular structures in a hobnailed "tombstone-like" arrangement, with additional areas containing trabeculae of osteoid and woven bone, with prominent osteoblastic rimming. The differential diagnosis at this point was either multifocal epithelioid hemangioma of bone or osteoblastomatosis. Immunohistochemistry showed strong expression of the vascular marker CD31, supporting a vascular neoplasm. The final diagnosis was multifocal epithelioid hemangioma with prominent reactive bone formation, an extremely unusual tumor with only one other similar case of multifocal disease reported in the literature. The patient was treated with curettage, cryosurgery, and bioceramic replacement and is currently doing well.